Legal Review of the Validity of a Power of Attorney to Sell as an Executorial Guarantee in a Breach of Performance Case : Case Study of Batang District Court Number 64/Pdt.G.S/2022/PN.Btg - Edward, Edward; Adawiyah, Rodiatun (IJBLE Scientific Publications Community Inc., 2025)
The power of attorney to sell is frequently employed as an alternative form of security in debt agreements outside of formal collateral mechanisms. Nonetheless, in practical application, such powers of attorney are often misused and treated as executorial guarantees, leading to legal complications when execution is attempted. This study seeks to assess the legal validity of a power of attorney to sell when used as an executorial guarantee in cases of default, and to evaluate the legal reasoning employed by the judges of the Batang District Court in Decision Number 64/Pdt.G.S/2022/PN.Btg. A normative juridical method was utilized, incorporating a statutory and case-based approach. Data were collected through literature reviews and judicial decision analyses and were examined using qualitative methods. The findings demonstrate that a power of attorney to sell cannot be equated with executorial collateral instruments such as mortgage or fiduciary security, as this contravenes the foundational principles of collateral law in Indonesia. The Batang District Court adjudicated that the said power of attorney lacked executorial force and thus required a civil lawsuit mechanism to execute the sale of the collateral. This judgment aligns with the principles of legal prudence and debtor protection, preventing potential abuse of legal authority. Accordingly, the use of a power of attorney to sell must be contextualized within its proper legal function and should not be construed as a substitute for executorial guarantees.